A proposal for implementing PBL in programming courses - Mora, Sonia (2014)
In the search of teaching strategies more consistent with the current needs of the industry and with the new university pedagogical model, an action research project was carried in the programming courses of the study program of Systems Engineering at the Universidad Nacional of Costa Rica (UNA). The project gradually introduced the principles of autonomy, collaborative learning and shared assessment. This paper reports the experience gained during the three years of the project in terms of a specific proposal for implementing the three principles in the area of programming. Aspects to be considered for an initiative of this kind to be successful are also presented.